010 Advanced glycation end products induce functional impairment in neonatal rat cardiomyocytes through enhanced production of reactive oxygen species. (22nd September 2015) - Hegab, Z; Gibbons, S; Mohamed, T; Schelcher, C; Shaheen, M; Oceandy, D; Neyses, L; Mamas, M A
Abstract : Advanced Glycation End products (AGEs) are formed through the non enzymatic glycation of proteins in conditions such as diabetes and may influence cellular function through actions on cell surface receptors, the most common of which (RAGE) belongs to the immunoglobulin superfamily of receptors. AGEs are implicated in the development of diabetic micro and macrovascular disease and are thought to be important in the development of heart failure in diabetic patients. For example, serum AGE levels have been correlated with a reduced survival and an increase in severity of heart failure. It is unclear is whether AGEs contribute to myocardial abnormalities observed in diabetes through direct myocardial actions. We have therefore investigated the effects of AGEs on cardiomyocytes and their potential mechanisms of action. Calcium (Ca 2+ ) transient amplitude was measured using field stimulation and Indo-1 dye, western blotting used for protein quantification, NF-KB luciferase assay to detect NF-KB activity and DHCF (dihydrochlorofluorscene) dye for ROS (reactive oxygen species) measurement. Western blot analysis showed that RAGE receptor is expressed in neonatal rat cardiomyocytes (NRCM) at 45 KDa. Incubation of NRCM with AGEs for 24 h at different concentrations, showed a dose response reduction of Ca 2+ transient amplitude with a maximum reduction (52±12%) at a concentration of 1 gm/l (p<0.01). No significant change was detected in the protein expression of Ca 2+ handling proteins. This was accompanied by a significant (24±1.4%) increase (p<0.01) in the production of reactive oxygen species (ROS) in AGE treated cells with significant increases in phosphorylation of both ERK1/2 (38±1.6%, p<0.05) and MAP kinase p38 (28±1.4%, p<0.05). A key target of AGEs in other tissues, the transcriptional factor NF-KB was shown by immunofluorescence to be translocated from the cytoplasm to the nucleus and using NF-KB luciferase assay, AGE treated NRCM showed dose dependant increase in luciferase activity with maximum response (2.5-fold induction) at the dose (1 gm/l for 24 h) supporting enhanced NF-KB activity. Both a NADPH oxidase inhibitor (enzyme that synthesises ROS; 10 ìM Apocynin) and a specific NF-KB specific inhibitor (100 nM of DPTC) inhibited Ca2+ transient suppression shown in AGE treated cardiomyocytes. This data demonstrate the presence and functionality of AGE receptors in myocardium. RAGE activation through a NADPH-dependent ROS pathway suppresses cytosolic Ca 2+ transients, through a NF-KB dependent process. These data provide insight into the mechanisms of myocardial damage in diabetes that occur independent of vascular disease through advanced glycation end products and may provide insight into key pathophysiological mechanisms occurring during the development of diabetic cardiomyopathy.